2008
DOI: 10.1158/0008-5472.can-07-5154
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-8 Functions as a Metastasis Suppressor through Modulation of Tumor Cell Adhesion and Invasion

Abstract: Collagenase-2 (matrix metalloproteinase-8, MMP-8) is an MMP mainly produced by neutrophils and associated with many inflammatory conditions. We have previously described that MMP-8 plays a protective role in cancer through its ability to regulate the inflammatory response induced by carcinogens. Moreover, it has been reported that experimental manipulation of the expression levels of this enzyme alters the metastatic behavior of human breast cancer cells. In this work, we have used mutant mice deficient in MMP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
155
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(169 citation statements)
references
References 49 publications
13
155
0
1
Order By: Relevance
“…According to the results of others (41,42), wildtype MMP-8 is a tumor protective factor. MMP-8 has the ability to inhibit melanoma progression and to reduce the metastatic potential of breast and lung cancer cells in both mice and humans.…”
Section: Discussionmentioning
confidence: 94%
“…According to the results of others (41,42), wildtype MMP-8 is a tumor protective factor. MMP-8 has the ability to inhibit melanoma progression and to reduce the metastatic potential of breast and lung cancer cells in both mice and humans.…”
Section: Discussionmentioning
confidence: 94%
“…Thirdly, the rs11225395 C-799T single-nucleotide polymorphism (SNP) at the MMP8 promoter region may affect the expression levels of MMP-8 and associate with early-stage disease (28). Fourthly, higher MMP8 mRNA levels in primary breast cancers are associated with reduced lymph node metastasis and with improved relapse-free and overall survival in nodenegative patients (29).…”
mentioning
confidence: 99%
“…From the viewpoint of a genomic study, some positive epidemiological findings reported that genotypes of promoter region of other MMPs such as MMP-1 and MMP-9, may serve as promising markers for the prediction of lung cancer susceptibility and prognosis (29)(30)(31). From the molecular viewpoint, MMP-8 might increase cell adhesion by rearrangement of cytoskeleton actin, thus decreasing cell invasion (32). However, there were few epidemiological studies investigating the role of MMP-8 polymorphisms in the susceptibility of cancers (33).…”
Section: Discussionmentioning
confidence: 99%